Analisis Peranan Sub Sektor Pertanian dan Sektor Unggulan dalam Pembangunan Ekonomi: Studi Kasus Provinsi Nusa Tenggara Barat - Azizah, Siti Nur; Azhari, Azhari (Universitas Batanghari Jambi, 2025)
Regional economic development is a process that aims to increase the yield of existing resources, create new jobs, and advance economic activities. This study is quantitative descriptive, using GDP data based on constant prices and economic growth of NTB province as well as Indonesia's GDP and economic growth during the period 2018-2022. The analysis was carried out using the Location Quotient (LQ) technique. The LQ value for the agricultural sector shows that the food crops sub-sector reached 2.33, horticultural crops 1.20, livestock 1.50, agricultural and hunting services 1.29, and fisheries 1.02. The flagship sector has an LQ value of 1.75, while mining and quarrying reaches 2.16. For the large trade and retail sectors, the LQ value is 1.02, transportation and warehousing 1.40, real estate 1.02, government administration 1.52, education services 1.49, health services 1.68, and other services 1.19. The agricultural sector in West Nusa Tenggara is the base sector, and this increase in income will drive demand for goods in the base sector, thus encouraging investment in the sector. The business sector of West Nusa Tenggara Province is divided into 4 classifications of each of these sectors, including: Superior Sector: There are Agriculture, Forestry and Fisheries Sectors, Mining Sector, Large Trade and Retail Sector; car and motorcycle repair, real estate sector, government administration sector, defense and compulsory social security, education services sector, health services sector and social activities, and other sectors.